Acts 1-9:42: Word Biblical Commentary - Walton, Steve, 1955- (Grand Rapids, Michigan : Zondervan Academic, 2024)
"The Word biblical commentary delivers the best in biblical scholarship, from the leading scholars of our day who share a commitment to Scripture as divine revelation. This series emphasizes a thorough analysis of textual, linguistic, structural, and theological evidence. These widely acclaimed commentaries serve as exceptional resources for the professional theologian, instructor, student, and everyone concerned with building theological understanding from a solid base of biblical scholarship."--
Introduction: A. What kind of commentary is this? ; B. The text of Acts -- Beginning at the beginnings (1-2) -- The mission in Jerusalem (3:1-8:3) -- Mission in Samaria and Syria-Palestine (8:4-12:25).
"Unless otherwise noted, all Scripture translations are those of the author"--Title page verso.
"General bibliography": pages 29-77.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Acts 1-9:42 - Word Biblical Commentary; Commentaries